Managing Tillage Operation and Manure to Restore Soil Carbon Stocks in Wheat–Maize Cropping System. (1st September 2019) - Khan, Ahmad; Fahad, Shah; Khan, Aziz; Saud, Shah; Adnan, Muhammad; Wahid, Fazli; Noor, Muhammad; Nasim, Wajid; Hammad, Hafiz Mohkum; Bakhat, Hafiz Faiq; Ahmad, Shakeel; Habib ur Rehman, Muhammad; et al.
Abstract : Increasing soil organic matter (SOM) contents improve the resilience of productive soil for future sustainability particularly in poor soil (<1% SOM). This study sought to elucidate how tillage and N fertilizer sources affect soil bulk density, soil organic carbon (SOC) and soil total N (TN) in 0‐ to 20‐cm soil depth. Treatments included minimum till (MT), conventional till (CT), deep till (DT), and twelve N treatments (60 and 120 kg urea N ha −1, 10 and 20 Mg farmyard manure [FYM] ha −1, 10 Mg soybean residue [SR] ha −1 and their combinations along with a control). The experiment was designed in randomized complete block design with split plot arrangement. Soil bulk density increased for DT toward the end of the experiment than CT or MT. The sequestration rates of SOC of MT was 22% higher than DT. The FYM retuned more SOC than SR, however SR returned more TN than FYM. Application of FYM as well as SR sequestered more C than urea or control. Conclusively, SOC returned was increased with 10 Mg FYM ha −1 along with 30 kg urea N ha −1 but TN with 10 Mg SR ha −1 in CT plots. This practice can therefore increase soil quality and productivity, and thus is considered a sustainable approach for soils deficient in organic matter. Core Ideas Minimum tillage improved C stock than shallow or deep tillage. The addition of urea increased SOC contents in SR plots than FYM. C Stocks in FYM and SR fertilized plots was about 3‐ to 4‐fold greater than control. Soybean residue build N stock principally in less plowed plots.